2019
DOI: 10.1136/bmjopen-2018-025127
|View full text |Cite
|
Sign up to set email alerts
|

Process evaluations of primary care interventions addressing chronic disease: a systematic review

Abstract: ObjectiveProcess evaluations (PEs) alongside randomised controlled trials of complex interventions are valuable because they address questions of for whom, how and why interventions had an impact. We synthesised the methods used in PEs of primary care interventions, and their main findings on implementation barriers and facilitators.DesignSystematic review using the UK Medical Research Council guidance for PE as a guide.Data sourcesAcademic databases (MEDLINE, SCOPUS, PsycINFO, Cumulative Index to Nursing and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
44
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(51 citation statements)
references
References 70 publications
(120 reference statements)
5
44
1
1
Order By: Relevance
“…For these reasons, there is an urgent need for approaches that address complex problems related to access and quality of health care [10]. However, a recent systematic review of process evaluation studies of complex interventions focused on chronic diseases found a lack of alignment between local needs expressed by stakeholders and the interventions implemented [13]. It was also found that limited knowledge of the health system could affect the implementation of interventions.…”
Section: Introductionmentioning
confidence: 99%
“…For these reasons, there is an urgent need for approaches that address complex problems related to access and quality of health care [10]. However, a recent systematic review of process evaluation studies of complex interventions focused on chronic diseases found a lack of alignment between local needs expressed by stakeholders and the interventions implemented [13]. It was also found that limited knowledge of the health system could affect the implementation of interventions.…”
Section: Introductionmentioning
confidence: 99%
“…The major strengths of this study lie in the application of existing theoretical frameworks – MRC guidelines and CFIR – that enabled a more systematic approach to data collection and analysis and also increases the replicability and generalizability of study findings [ 7 , 39 ]. Additionally, triangulation of qualitative and quantitative data provides different perspectives on aspects of program implementation.…”
Section: Discussionmentioning
confidence: 99%
“…As in many other process evaluations, we will use maximum variation sampling on sociodemographic characteristics and baseline adherence, alongside triangulation, to minimise the risk of bias. 102 Additionally, readers should be aware that small-scale feasibility work does not generalise in every regard when scaled up in larger scale studies. 103 104 Finally, early health economic modelling of the cost-effectiveness, 105 was not updated as part of this feasibility work, but will be revisited in 2021 as part of the full-scale evaluation.…”
Section: Discussionmentioning
confidence: 99%